Effectiveness of Animal-Assisted Therapy in the Pediatric Population: Systematic Review and Meta-Analysis of Controlled Studies (2018)
OBJECTIVE: To synthesize the results of controlled studies evaluating the effectiveness of animal-assisted therapy (AAT) in children. METHODS: Eleven databases were searched following the Preferred Reporting Items for Systematic Reviews and Meta-analyses statement recommendations, and references from included studies and previous reviews were examined. No date or language filters were applied. Only controlled study designs, including those using wait-list controls, that studied a specific condition or illness were included. Study quality was assessed using the Cochrane Risk of Bias Tool. RESULTS: Twenty-six studies that met the inclusion criteria were retrieved. Nine were conducted in children with autism spectrum disorders, 10 in cerebral palsy (CP), 2 in Down syndrome, 3 in pain, and 2 in other conditions. Qualitative synthesis showed a small but significant contribution of AAT to the management of these conditions. Meta-analysis showed a mean difference in improvement in the Gross Motor Function Measure-66 scale in children with CP of 1.61 (95% confidence interval [CI] -2.00 to 5.23) and a mean difference for 5-point pain scales of -0.81 (95% CI -1.32 to 0.30), both favoring AAT. CONCLUSION: Animal-assisted therapy may be useful as a complementary intervention in the management of children with CP and pain. Although results are in general positive for the management of children with Down syndrome and autism, the diversity of scales used to measure outcomes makes it difficult to establish true effectiveness. The application of simple corrective measures in the randomization process would greatly improve the quality of evidence. It is necessary to reach a consensus between AAT researchers regarding appropriate instruments to provide higher-quality evidence in further studies.